The SeaRAS AquaSense™ System: Real-Time Monitoring of H2S at Sub µg/L Levels in Recirculating Aquaculture Systems (RAS) - Lien, Eldar; Valsvik, Geir; Nordstrand, Jan Vidar; Martinez, Vincent; Rogne, Vegard; Hafsås, Ola; Queralt, Sara; Fathi, Behnood Sjåstad; Aga, Morten (Frontiers in Marine Science, 2022)
Hydrogen sulfide (H2S) is toxic to all species used in aquaculture, causing H2S-poisoning that can lead to significant economic losses. Called the silent killer among experts, H2S is highly soluble in water with significant damage potential; once detected, the time for mitigation actions is limited. H2S detection at µg/L is challenging with today’s sensors. The industry, however, was not able to provide a reliable yet user-friendly system for this. The aim of this paper is to introduce a system for real-time monitoring of H2S at µg/L levels in RAS. The SeaRAS AquaSense System (AQS) utilizes real-time monitoring of H2S in parallel with other water quality parameters, such as CO2, O2, pH, and temperature, through a set of autonomous wireless-based sensor units installed in multiple locations in RAS. The system is calibrated and verified further by an autonomous calibration system where substrates of known values are brought to the sensor at a defined interval, offering the user data confidence that is exceptional and of high value. The H2S levels are measured at high-temporal resolution (down to 0.05 µg/L). By using AQS units in distinct locations in RAS-process, true real-time monitoring of water treatment loop is given. Preliminary results provide new insights to H2S formation mechanism in operational RAS, and, more important, provide a basis for the risk mitigation through degassing in RAS. A true mass balance of the system can be formulated through collected data from AQS units. Via using AQS, it is also possible to track the amount of H2S that is leaking to the recirculating water per m2 of biofilm in RAS. This is a critical and of high priority parameter in coping with H2S-induced risks in RAS. The finding of this work highlights the continuous H2S-formation in RAS, ergo, the industry should instead focus in how to cope with it. In this regard, AQS comprises a step forward towards a practical solution for managing H2S-risks in aquaculture. This work suggests a need for future research on determining acceptable limits for H2S and investigating its possible interaction with other parameters like CO2 in water quality context in RAS.